Hubungan Antara Risiko Postur Kerja Dengan Risiko Keluhan Muskuloskeletal Pada Pekerja Bagian Pemotongan Besi Di Sentra Industri Pande Besi Padas Klaten - Suwanto, Joko, Tarwaka, PGDip, Sc, M. Erg, Kusuma Estu Werdani, SKM., M.Kes (2016)
Musculoskeletal complaints is one of the occupational diseases that arise in the workplace. Musculoskeletal complaints occur one of them due to work postures that are not good. Posture is the position of the body segments working at the time of doing the job. This study aims to determine the relationship between the risk of working with risk posture Musculoskeletal complaints on the part of workers in the metal cutting industry Sentra Pande Besi Padas Klaten. This research method using observational design with cross sectional approach. Subject of the study a total of 35 workers by using total sampling. REBA posture assessment and assessment using Musculoskeletal using NBM. Statistical test using the Spearman Rank (Rho) with a significant level (α≤0,05). Statistical test results between the risk posture of the work with risk Musculoskeletal complaints obtained significant values (p = 0.001) with a moderate level of closeness relationship (r = 0.551). The conclusions of this study there was a significant association between the risk of working with risk posture Musculoskeletal complaints. It can be recommended that workers doing repairs position at work, doing stretching and employers do repair work and carry out engineering work on the tool. Key word : work posture, musculoskeletal, iron worker